PENGEMBANGAN MODUL BERNUANSA MIND MAP YANG EFEKTIF PADA MATERI SISTEM REGULASI MANUSIA UNTUK SISWA KELAS XI IPA SEKOLAH MENENGAH ATAS - Itgo Hatchi; Lia Purnama Sari (Jurnal Education and Development, 2019)
This article was written to describe the result of mind map nuance module on human regulatory system material development for grade XI students. The development was done by implementing four-D model. Based on the research revealed that the module developed is at very valid category with value 84.44%. Thus, it can be concluded that the mind map nuance module on human regulatory system material for gade XI student in senior high school is effective